Gene expression of inflammasome components in peripheral blood mononuclear cells (PBMC) of vascular patients increases with age - Wu, Xiaoyu; Hakimi, Maani; Wortmann, Markus; Zhang, Jian; Böckler, Dittmar; Dihlmann, Susanne (Immunity & ageing, 2015)
Chronic low-grade inflammation is considered a driver of many age-related disorders, including vascular diseases (inflammaging). Inhibition of autophagic capacity with ageing was postulated to generate a pro-inflammatory condition via activation of inflammasomes, a group of Interleukin-1 activating intracellular multi-protein complexes. We thus investigated gene expression of inflammasome components in PBMC of 77 vascular patients (age 22-82) in association with age.